Poly-(L-homoarginine) for the non-invasive treatment of endophthalmitis - Ting Hua; Tianzi Zhang; Yi Tang; Shuo Wang; Guowenlie Gao; Chunsheng Xiao; Pengqi Wan; Hong Wu (Materials Today Bio)
Bacterial endophthalmitis (BE) is a severe eye infection that often leads to vision loss or blindness. The conventional therapeutic approach entails the administration of intravitreal antibiotic injections, a procedure that is associated with significant discomfort for the patient. Here, we present a kind of poly-(L-homoarginine) (C6PLL10-Gua) as a non-invasive alternative for effectively eliminating bacteria in endophthalmitis. The synthesized C6PLL10-Gua effectively kills various bacteria by disrupting cell membranes, without causing bacteria resistance over 14 generations. More importantly, C6PLL10-Gua demonstrated significant tissue permeability both in vivo and in vitro. This kind of C6PLL10-Gua eye drops were capable of effectively traversing the ocular barrier to access the posterior segment of the eye. After being instilled into the conjunctival sac, C6PLL10-Gua enabled rapid (<30 min) and prolonged (>24 h) distribution in the retina via a noncorneal pathway. Furthermore, in a MRSA induced endophthalmitis rat model, topical instillation of C6PLL10-Gua showed significant therapeutic effect, which presenting a promising non-invasive therapeutic approach for managing endophthalmitis.